Trend Wisata Kuliner melalui Olahan Produk Pasta - Agus Wibowo Setyo Budi Santoso (Media Wisata, 2019)
Pasta has been the most popular foreign food among food lovers in Yogyakarta. This food mostly founded in Steak restaurant. Javanese noodle resstaurant, etc. Because of its popularity towards culinary entrepreneur, they try to combine the making of main composition of pasta that is halal-guaranted for the lovers.This writing is based on the experiment of main compotition of pasta . Pasta that is made from wheat flouris combined with Belitung caladium flour (Xanthosomasagittifolium). This experiment is did in 5 combinations as a sample experiment and each is rated in color, taste, aroma, and texture.The aim of this experiment is to find the most ideal combination for pasta based on its color, taste, aroma, and texture. As the result of this experiment, in the color aspect, the first and the fourth combination is different. The taste aspect contains differences among the first, third, and fourth combination, so do the aroma aspect and the texture aspect.It based on probability value of 95% or critical level of 0,05 in examining hypotheses. If probability value is less than 0, 05, it is said there is a significant difference. The table tells the color of first combination is different from forth combination. The smell of first combination is different from third and forth combination. The texture of first combination is different from third and forth combination.There is no different combination of 25% caladium flour. It shows pasta which is made by combination 25% of Belitung caladium flour has highest probability value from any compositions and all aspect. Probability value is higher than 0,05. It means pasta which is made by combining 25% of Belitung wheat flour has highest quality or highest significance value. The final experiment is combining 25% caladium flour and 75% shows close smell, taste, and pasty color. However, this color is more interesting to the respondents than other combination. It also has close texture to original